PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA - Fitria Alfiani; Sri Utaminingsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problem in this study is the difficulty students face in understanding mathematical concepts, resulting in incomplete mathematics learning. The objective of this research is to improve the conceptual understanding of mathematics among third-grade students at SDN 1 Bakalan Krapyak through the implementation of a contextual learning model. This study employs Classroom Action Research (CAR) conducted over two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 23 third-grade students. Data collection techniques included observation, interviews, and learning outcome tests. The results show an improvement in students’ conceptual understanding in each cycle. The average class score increased from 72 in the first cycle to 82 in the second cycle. The percentage of students achieving mastery learning improved from 65.2% in cycle I to 82.6% in cycle II. It is concluded that the contextual learning model successfully enhanced students’ conceptual understanding, having met the success criteria of an average score of ≥ 70. Teachers are encouraged to fully utilize contextual learning not just as an alternative, but as a primary teaching method.